The process of dying/death: intervening conditions to the nursing care management - Roberta Teixeira Prado; Josete Luzia Leite; Ítalo Rodolfo Silva; Laura Johanson da Silva; Edna Aparecida Barbosa de Castro
ABSTRACT Objective: To exhibit the factors that influence the Nursing care management in the face of death and the process of dying/death of hospitalized adults in the medical-surgical units for hospitalization. Method: The Grounded Theory was applied with the theorical support of the Complex Thinking Theory. Data have been collected through semi-structured interviews from May, 2015 to January, 2016 with three sample groups totaling 41 participants: nurses, assistant nurses and members of multidisciplinary group. Data analysis followed the steps of open coding, axial coding and selective coding. Results: The category "Pointing out the interfaces of care management to patients in process of death/dying and their families" and its respective subcategories show the complex interactions established by the nurse due to the Nursing care management. Final considerations: Subjective, educational, sociocultural and institutional conditions influence the nurse interactions, causing order/disorder on care management.